2020
DOI: 10.3390/sym12060883
|View full text |Cite
|
Sign up to set email alerts
|

Investigating on the Iconic Gas Compositions Produced by Low-Temperature Heating Cotton

Abstract: This study aims at achieving the generation laws of the iconic gas compositions produced during the process of the cotton smoldering. A mini tube furnace was used to heat a long-staple cotton sample from Xinjiang, China, and a gas chromatography-mass spectrometer (GC/MS) was applied to analyze the produced organic and inorganic gas composition at different low temperatures ranging from 95 °C to 185 °C. Besides, a thermogravimetric experiment under air atmosphere was done in order to verify the correctness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Another study on the cotton smoldering process was proposed in 2020, which gives generation laws of the iconic gas compositions during cotton smoldering Su et al, [12]. They used a minitube furnace for heating the cotton sample which was collected from Xinjiang, China.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study on the cotton smoldering process was proposed in 2020, which gives generation laws of the iconic gas compositions during cotton smoldering Su et al, [12]. They used a minitube furnace for heating the cotton sample which was collected from Xinjiang, China.…”
Section: Related Workmentioning
confidence: 99%
“…(3) The previous systems did not investigate and integrate the phenomena of spontaneous combustion in their proposed architecture (4) In the past few years, very limited research done in domain of cotton quality, most authors studied only factors and risk of combustion in cotton [3,9,10], the igniting behavior of cotton contaminated with oil [5], comparative studies of cotton and flame combustion [6], the flammability of cotton bales that was evaluated [7], and research done to investigate IoT role in the cotton warehousing environment [11]. Some authors also investigate iconic gases produced during the low-temperature heating process of cotton [12], which helps to identify major gases produced during cotton heating. Some authors also proposed solutions to measure and control external weather conditions in the storage area only, and they aim to improve safety mechanisms there [3,8,11] The current research provides a wireless sensor network (WSN) and machine learning-(ML-) based models for cotton storage monitoring which provides (1) Efficient real-time sensing of major factors contributing to spontaneous combustion using WSN…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they concluded that prevention is not only a means of preserving cotton during its storage and the heating process; rather, it is necessary to conduct research on the storage of raw cotton components. 2020) found iconic gas compositions via the low-temperature heating of cotton [17]. They proposed laws for iconic gas compositions that may be produced during the process of the cotton smoldering.…”
Section: Related Workmentioning
confidence: 99%
“…We came to the conclusion, after a detailed literature survey, that only limited experimental methods have been developed to check the self-heating and spontaneous ignition of agricultural products, e.g., coal, wheat, and hay [5,[16][17][18][19][20][21], including basket heating, the crossing-point temperature method proposed by Worden (2011), thermogravimetric analysis (TGA) conducted by Khattab (1999), the Ordway apparatus used by Thompson (1928), and the Mackey apparatus method proposed by Khattab et al (1999) [22]. Also, some researchers proposed solutions to measure and control external weather conditions of the storage area only, and they aim to improve safety mechanisms there [16,20,21]; one study focused on chemical processes to identify gases produced during smoldering [17], and little work has been done to investigate factors contributing to SC and its effect on cotton quality [5,19]. There is a big research gap in the detection and prevention of cotton smoldering, SC and cotton quality maintenance during storage.…”
mentioning
confidence: 99%